1995
DOI: 10.1001/jama.1995.03530040033037
|View full text |Cite
|
Sign up to set email alerts
|

Preventable Hospitalizations and Access to Health Care

Abstract: Communities where people perceive poor access to medical care have higher rates of hospitalization for chronic diseases. Improving access to care is more likely than changing patients' propensity to seek health care or eliminating variation in physician practice style to reduce hospitalization rates for chronic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
435
2
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 726 publications
(464 citation statements)
references
References 9 publications
24
435
2
3
Order By: Relevance
“…Our findings are therefore limited to COPD and asthma, and may not be generalisable to other LTCs. 20,[182][183][184] However, the decision-making process that patients with LTCs use to determine whether or not to use unscheduled care is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are therefore limited to COPD and asthma, and may not be generalisable to other LTCs. 20,[182][183][184] However, the decision-making process that patients with LTCs use to determine whether or not to use unscheduled care is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…5 Another metaanalysis found that 68% of patients who committed suicide did not have contact with mental health services in the year before suicide. 4 The association between decreased ambulatory treatment of NPPDs and SUDs and hospitalization remains unknown, although this has been well established for chronic medical conditions, 12 and there is no reason to think that it would not apply to mental disorders. It is currently unknown whether shortening the period of untreated illness would result in reduced health care expenditures, morbidity, and mortality; however, the association between lack of care and greater mortality related to suicide and overdose suggests the need for interventions to improve active care of psychiatric conditions.…”
Section: The Association Of Untreated Illness With Morbidity and Mortmentioning
confidence: 99%
“…Based on a sample of 6000 full ED records, the algorithm classifies visits on the basis of discharge diagnosis as 1) non-emergent, 2) emergent/primary care treatable, 3) emergent -ED care needed -preventable/avoidable and 4) emergent -ED care needed -not preventable/avoidable. [24,25] ED visits resulting in discharge rather than admission was…”
Section: Literature Searchmentioning
confidence: 99%